Corporate governance, ownership structure and bank performance - Aintablian, Sebouh (2008)
We study the relationship between ownership structure and performance for a sample of 89 commercial, investment, specialized, and Islamic banks in the Middle East and North Africa (MENA) region for the period 1998-2003.) Our results for commercial banks show that the performance of banks is weakened with board/management separation and concentrated ownership, and enhanced with government ownership.